Influence of electric current pulses on the solidification of Cu-Bi-Sn immiscible alloys - Hongxiang, Jiang (Sci Rep, 2015)
Continuous solidification experiments were carried out with Cu-Bi-Sn alloys under the effects of Electric Current Pulses (ECPs). A model describing the microstructure evolution was developed. The formation of the microstructure in the continuously solidified alloys was calculated. The calculations demonstrated that ECPs mainly affect the solidification process through changing the energy barrier for the nucleation of the minority phase droplets (MPDs). When the matrix liquid has a lower electric conductivity compared to the MPD, the ECPs lead to a decrease in the energy barrier for the nucleation of the MPDs which then promote the formation of a finely dispersed microstructure. When the matrix liquid has a higher electric conductivity compared to the MPD, the ECPs cause an increase in the energy barrier for the nucleation and lead to the formation of a phase segregated microstructure.